The Publishing of Economic Papers and Its Impact on Graduate Faculty Ratings, 1960-1969. - Siegfried, John J. (Journal of Economic Literature, 1972)
I am grateful to Professors Ralph Andreano, Arthur S. Goldberger, and W. Lee Hansen of the University of Wisconsin for their encouragement and comments on an earlier draft of this paper. Many valuable suggestions were contributed by two anonymous referees and the participants in the Workshop in Applied Welfare Economics at the University of Wisconsin, Fall 1970, especially Morley Gunderson. Charles Leitzke assisted in the arduous task of data collection. The usual caveat is applicable.